Larvicidal Effect of Medicinal Plants Against Aedes aegypti (L.) (Diptera: Culicidae) in Mexico - Reyes-Villanueva, Filiberto; Gonzales-Gaona, Othón; Rodríguez-Perez, Mario (BioAssay, 2009)
Some phytochemicals comprise toxic compounds that can be exploited in the control of mosquito larvae. Therefore, larvicidal effect of aqueous extracts of 14 medicinal plants at 0.05% (weight: volume) was evaluated against Aedes aegypti (L.) in Mexico. Bioassays were conducted with early fourth instars submerged in plant infusions to ingest the potential insecticide compounds. A preliminary bioassay for all plants showed that the highest mortality occurred in extracts from crushed and whole plants. The mean mortality for Solanum nigrescens Martens & Galeotti, Operculina pteripes (G.Don) O’Donell and Phoradendron tamaulipensis Trel. was 55, 17.5 and 5.8% respectively. Then, monthly bioassays with fresh field-collected S. nigrescens were conducted to evaluate seasonal variation in larvicidal activity with different plant parts. Only extracts of crushed (83-100% mortality) and entire (88 – 98% mortality) root were lethal to A. aegypti larvae. Monthly average mortality was 91.6 and 93.3% for crushed and whole root extracts of S. nigrescens. These findings can be exploited to developed ecologically friendly products to be integrated with other control tactics in dengue vector control program in Mexico.